Peiminine Exerts Its Anti-Acne Effects by Regulating the NF-κB Pathway - So Jin Cha; Seon Sook Kim; Jin Hak Shin; Su Ryeon Seo (MDPI AG, 2024)
Peiminine is the main natural alkaloid compound extracted from the Chinese herb Fritillaria. Although peiminine is known for its antioxidant and anti-inflammatory effects in conditions such as mastitis and arthritis, its impact on inflammation induced by Cutibacterisum acnes (C. acnes) has not been explored. The aim of this study was to investigate the effect of peiminine on C. acnes-induced inflammatory responses in the skin and to identify the underlying mechanism involved. We discovered that peiminine inhibits the C. acnes-induced expression of inflammatory mediators such as pro-interleukin-1β (pro-IL-1β), cyclooxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) in mouse bone marrow-derived macrophages (BMDMs). Peiminine suppressed the activation of nuclear factor-kappa B (NF-κB) without affecting the activation of mitogen-activated protein kinase (MAPK) pathways such as JNK, ERK, and p38 MAPK. In addition, we found that peiminine suppressed inflammatory cytokine expression and ameliorated histological symptoms in C. acnes-induced mouse skin. Our study is the first to provide evidence that peiminine has an inhibitory effect on acne, and it points toward the potential of incorporating peiminine into cosmetic and pharmaceutical formulations for acne treatment.